Phase II study of oral docetaxel and cyclosporine in canine epithelial cancer. (21st August 2012) - Waite, A.; Balkman, C.; Bailey, D.; Kiselow, M.; Flory, A.; Beaulieu, B. B.; Lewis, L. D.; McEntee, M.
Abstract The goal of the current study was to determine the efficacy of oral docetaxel in combination with cyclosporine in the treatment of canine epithelial cancer. Requirements for eligibility were histological confirmation of epithelial neoplasia, measurable disease, no chemotherapy treatment within 2 weeks, and a life expectancy of ≥3 months. Fifty‐one dogs were enrolled. All dogs received 1.625 mg kg−1 of docetaxel with 5 mg kg−1 of cyclosporine (DT/CSA) by gavage. Ten dogs had progressive disease at 2 weeks, one dog died, and one dog was withdrawn from the study. Thirty‐nine dogs were given a second dose of DT/CSA, three each receiving a third or fourth dose. Eight dogs had a dose reduction (1.5 mg kg−1) and six dogs had treatment delays primarily for gastrointestinal toxicity. The overall response rate was 16.7% (8/48 had a partial response there were no complete responses). The highest response rate was seen in dogs with oral squamous cell carcinoma (50%; 6/12).